Department of Veterinary Anatomy and Histology College of Veterinary Science and AH, Anand Agriculture University, Anand-388001 - Ambade, RB; Dalvi, SH; Gatne, MM; Dighe, VD; Doiphode, AY (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The aim of the present study was to determine the stress enzyme level during different seasons in Pandharpuri Buffalo. The study was conducted on 10 healthy Pandharpuri buffaloes more than 2 years of age. All the animals were maintained under standard feeding and management practices. Temperature Humidity Index (THI) was calculated from meteorological data for the different seasons. Five ml blood was collected from each buffalo aseptically from jugular vein once in the Month of May, August and December. Serum was separated by centrifugation from each blood sample and was used for estimation of activity of stress enzymes. Mean ± S.E. THI was 76.97 ± 0.38, 73.32 ± 0.38 and 68.81 ± 0.49 for summer, rainy and winter season, respectively. Mean ± S.E. activity of SOD (U/ mg of protein), CAT and GPx was 52.41± 1.49, 39.55± 1.92 and 32.54± 0.70; 61.84 ± 2.23, 43.98 ± 3.57 and 29.304 ± 1.51 and 0.374 ± 0. 05, 0.232 ± 0.01 and 0.128 ± 0.20 during summer, rainy and winter seasons, respectively. All the serum antioxidant enzymes were found to be significantly (P < 0.05) higher in the summer season compared to the rainy and winter seasons. to dissipate heat. As a part of defence against Livestock plays an important role in rural economy through its contribution to food, employment generation and drought power. Buffalo has been the mainstay of rural economy in the Indian subcontinent and South East Asian countries. Most of the domestic animals are able to maintain equilibrium between the heat production and heat loss under thermoneutral zones. Heat stress has many detrimental effects on livestock (Marai and Habeeb, 2010). High ambient temperature, relative humidity and radiant energy compromise this ability of animals the menace of reactive oxygen species, the body employs antioxidants to quench these free radicals. The antioxidant enzymes superoxide dismutase (SOD), catalase and glutathione peroxidase (GPx) act by scavenging both intracellular and extracellular superoxide radical and preventing lipid peroxidation of plasma membrane. The activities of antioxidant enzymes and lipid peroxidation alter signiûcantly during oxidative stress. So, they can be used as markers of oxidative stress. Glutathione peroxidase functions in cellular redox reactions to protect the cell membrane from oxidative damage caused